The Effect of Metacognitive Judgment and Spaced Rehearsal on Map Learning - Patron, Kishandra Anne E. (Tufts Archival Research Center, 2021)
Map learning comprises the use of bird’s-eye-view representations of an environment to encode spatial information, such as the locations and distances between landmarks. In the present study, I used a Judgment of Learning (JOL) methodology to examine the role of explicit metacognitive monitoring and study repetition in map learning. Researchers investigate the role of metacognitive monitoring in learning by measuring participants’ JOLs, which are predictions of future success at recalling learned information. Previous work using word pairs argued that producing JOLs may affect control processes and enhance memory by influencing people’s learning goals, a phenomenon called JOL-reactivity. In my experiment, participants studied one block of landmark pairs in a verbal context and another block in a spatial context. In each block, participants studied half the landmark pairs one time and half the landmark pairs three times. Following study, participants either produced delayed JOLs to studied items or completed delayed random number generation (RNG), also in context of the studied items. Participants lastly tested their memory in a non-spatial context. We found that participants recalled stimuli more accurately when study and test spatial contexts aligned. Moreover, participants produced more accurate JOLs when they studied stimuli three times in the same spatial context as test. My experiment offers preliminary and exploratory insight into how metacognitive monitoring and restudy impact map learning. Through greater understanding of the relationships between metacognition and map learning, we can better monitor our learning of new environments to shape more accurate map recollection during future test.